Assessment of Genetic Diversity in Jatropha Curcas (L.) Germplasm from India Using Rapd Markers - Dhillon, R. S.; Jatian, M.; Singh, Charan; Rizvi, R. H.; Rani, T. (Indian Forester, 2012)
Random amplified polymorphic DNA (RAPD) markers were used to evaluate the genetic diversity among populations of Jatropha curcas (L.) from different agro-climatic regions of India. Out of 305 amplified bands obtained with 30 primers, 291 were found polymorphic. The polymorphisms were scored and used in band-sharing analysis to identify genetic relationship. Evaluated accessions were grouped into two main clusters except MP-020 from Ratlam (Madhya Pradesh) was out crouped from rest of accessions at a similarity coefficient of 0.50. Based on Jaccard’s coefficient of similarity values, the maximum similarity was found between accessions MP-022 and MP-031 (0.95). Molecular diversity among the accessions was low at a level of 30 per cent, indicating the need of widening the genetic base of J.curcas through various means.